The Poverty and Welfare Impacts of Climate Change Quantifying the Effects, Identifying the Adaptation Strategies - Skoufias, Emmanuel (Washington, DC: World Bank, 2012)
The continued decline in global poverty over the past 100 years particularly in the past three decades is a remarkable achievement. In 1981, 52 percent of the world population lived on less than $1.25 a day. By 2005, that rate had been cut in half, to 25.0 percent, and by 2008 to 22.2 percent (World Bank 2012). Preliminary estimates for 2010 indicate that the extreme poverty rate has fallen further still; if follow-up studies confirm this, the Millennium Development Goal (MDG) of halving world poverty will have been reached five years early (World Bank 2010). In recent years, poverty reduction has continued in most countries, even after the financial, food, and fuel shocks of 2008-09. Although poverty remains widespread in South Asia and Sub-Saharan Africa, progress has been substantial: extreme poverty fell in South Asia from 54 percent in 1990 to 36 percent in 2008 (World Bank 2012). In Sub-Saharan Africa, where population growth exceeded the rate of poverty reduction, the number of extremely poor people increased from 290 million in 1990 to 356 million in 2008, yet over 2005-08, the region's poverty rate nonetheless 'fell 4.8 percentage points to less than 50 percent the largest drop in Sub-Saharan Africa since international poverty rates have been computed,' according to the latest edition of the World Development Indicators (WDI) (World Bank 2012). Although progress has been slower at the $2-a-day poverty line, the WDI noted that an increase in the absolute number of people living on $1.25-$2.00 a day reflects both the upward movement from extreme poverty and 'the vulnerabilities still faced by a great many people in the world.' climate change is likely to reduce agricultural productivity, especially in the tropical regions, and to directly affect poor people's livelihood assets including health, access to water and other natural resources, homes, and infrastructure (World Bank 2010). Moreover, increasing climatic variability manifesting as more frequent and erratic weather extremes, or 'weather shocks' will likely make poor households even more vulnerable, which could in turn exacerbate the incidence, severity, and persistence of poverty in developing countries. This volume not only surveys the research terrain concerning the effects of climate change on poverty but also looks closely at vulnerable rural populations (in a developing country, Indonesia, and in the newly industrialized Mexico) where weather shocks have measurable short term if not immediate effects on the farming livelihoods many depend on for both income and subsistence. The low-income farmers of rice in Indonesia and of corn and other staple crops in Mexico are at the human forefront of climate change.